2013
DOI: 10.1155/2013/172529
|View full text |Cite
|
Sign up to set email alerts
|

A Mathematical Model for Thermosensitive Liposomal Delivery of Doxorubicin to Solid Tumour

Abstract: The effectiveness of anticancer treatments is often hampered by the serious side effects owing to toxicity of anticancer drugs and their undesirable uptake by healthy cells in vivo. Thermosensitive liposome-mediated drug delivery has been developed as part of research efforts aimed at improving therapeutic efficacy while reducing the associated side effect. Since multiple steps are involved in the transport of drug-loaded liposomes, drug release, and its uptake, mathematical models become an indispensible tool… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
53
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(60 citation statements)
references
References 33 publications
6
53
0
Order By: Relevance
“…The diffusivity of doxil liposomes was based on broad -field fluorescence measurements of nanoparticles of similar size and mass within agar gel phantoms (in vitro) [33]. Many nanoparticles diffuse on the order of 10 -11 cm 2 /s in mucus covered epithelial tissues [34], but the selection of D tiss = 1.0x10 -9 cm 2 /s is closer line with previous simulations of doxil [35], and yields a similar drug penetration in the tumor, due to the square root dependence on diffusivity on permeation length.…”
Section: Drug Diffusion In the Vasculature And Surrounding Tissuessupporting
confidence: 79%
See 2 more Smart Citations
“…The diffusivity of doxil liposomes was based on broad -field fluorescence measurements of nanoparticles of similar size and mass within agar gel phantoms (in vitro) [33]. Many nanoparticles diffuse on the order of 10 -11 cm 2 /s in mucus covered epithelial tissues [34], but the selection of D tiss = 1.0x10 -9 cm 2 /s is closer line with previous simulations of doxil [35], and yields a similar drug penetration in the tumor, due to the square root dependence on diffusivity on permeation length.…”
Section: Drug Diffusion In the Vasculature And Surrounding Tissuessupporting
confidence: 79%
“…Molecular diffusion constants through the interstitial space of living tissues are more difficult to obtain and are likely to vary between different tissue types. For the present study, we estimated tissue diffusivity for doxil liposomes to be 1x10 -9 cm 2 /s, in line with previous studies [35], [36], [66]. Varying the diffusivity by five orders of magnitude (10 -10 -10 -5 cm 2 /s) allowed us to implicitly investigate the impact of drug weight, size, polarity, and interaction with endothelia and tissue environments (see Figure 4).…”
Section: Comparison With In Vitro and In Vivo Studiessupporting
confidence: 73%
See 1 more Smart Citation
“…By using the experimental data in [61] for liposome exposure to ultraviolet light, the value of l  = 0.000104 min -1 is adopted in our work. 20 In this work, we use t  = 0.0078 min -1 [62] obtained by using the best fitting curve on nonlinear least square methods for experimental data obtained at 42°C [63].…”
Section: Simulation Results and Discussionmentioning
confidence: 99%
“…65,66 Use of another computational tool has demonstrated that superior antitumour effects can be achieved using delivery of thermosensitive liposomes relative to continuous infusion over 2 h, and that the localization afforded by thermosensitive drug delivery leads to lower drug concentrations in normal tissues. 67 Other models have been useful in aiding our understanding of doxorubicin pharmacokinetics and drug delivery, as well as its effects on cellular biology and function. [68][69][70] Trastuzumab-induced cardiotoxicity…”
Section: Reviewsmentioning
confidence: 99%